Numerical study of irregular wave overtopping and overflow - Soliman, Akram S M (2003)
Wave overtopping is one of the most important processes for the design of seawalls. During the past 50 years methods for predicting wave overtopping of coastal structures have continuously been developed. However, it is evident from the existing literature that additional investigations into overtopping of small positive, zero and negative freeboard are needed. The present thesis describes numerical investigations based in this background. Wave overtopping is dependent on the processes associated with wave breaking. Therefore, a two dimensional breaking wave numerical model has been developed and used to study the phenomena of wave overtopping. The model is based on the Reynolds averaged Navier-Stokes equations for the mean flow and k-epsilon equations for turbulent kinetic energy, k, and the turbulence dissipation rate, epsilon. The model accuracy in simulating propagation of linear and irregular waves has been evaluated. The overall performance of the model is considered satisfactory. The development of guidelines for calculating overtopping discharge for different seawall slopes is presented. All slopes have been subjected to a wide range of irregular waves. The influence of how the slopes of seawalls, wave type (breaking and non-breaking) and crest freeboard affect the overtopping discharges has been investigated. Based on the numerical data, a new expression for breaking and non-breaking waves on smooth impermeable slopes is proposed. With the new expression it is possible to predict overtopping discharges of smooth seawalls in small positive, zero and negative freeboard.